The Meaning of Murder: family Members in the Lives of Juvenile Homicide Offenders - Deegan, Simone Jessica (The British journal of criminology, 2021)
This article underscores the litany of problems that arise for significant others when a juvenile is convicted of murder. It focuses on how these individuals confront the precise nature of their child’s criminality while simultaneously defending themselves against a series of attacks from a variety of intra- and extra-familial sources. A major conclusion of the article is that murderers’ relatives disappear into an eternal vortex of guilt, shame and anger with little, if any, formal or informal support as a means to manage or recover from the debilitating stigma and strain.